Considering the this-worldly religious focus of the African traditional worldview as found in South Africa - Henry, Desmond; Malan, Jacques (Verbum et Ecclesia, 2017)
Most articles evaluating the African traditional worldview focus an attack on the ancestor cult or highlight positive aspects of the worldview. In either case, mention of the this-worldly religious focus tends to be ‘in passing’. An evaluation of this aspect of the worldview is a gap in the research, which this article seeks to address. The findings should significantly affect evangelical ministry method to many people in the country. The this-worldly religious focus of the African traditional worldview as found in South Africa is considered. It is a focus which hardly, if ever, looks beyond this world and this age. The this-worldly focus is a significant feature of the African traditional worldview and related African Traditional Religion (ATR). The concern raised is that this feature of the worldview is prevalent in the country, is unbiblical and is a major problem affecting the church. The article first describes the this-worldly religious focus and how it is expressed in ATR and in those strongly influenced by ATR. It then discusses its prevalence in South Africa. A biblical evaluation is then done, considering what the Bible has to say on the matter and considering the views of some evangelicals. Finally, some proposals are made for responding to the challenge. There are significant steps that can be taken to counteract the problem and so design evangelism and discipleship that the African believers are moved to resist rather than follow the this-worldly religious focus and so more faithfully follow the way of our Lord.
free
Keywords: Christianity and African religions; Culture and religion; Folk religion; African; South Africa – Religion; South Africa.